Ensuring Victims’ Participation in the Criminal Justice of Bangladesh - Rahman, Khandaker Farzana (International Journal of Criminology and Sociology, 2022)
It is seen that if the main actors in a criminal justice framework are to be identified, the most commonly identified would be the alleged, his legal representative, the prosecutor and the judge. In our current legal system, the victim appears to be one of the overlooked and disregarded parties, when in reality they should be considered a vital stakeholder in the criminal justice process to secure justice. Due to adversarial legal system in Bangladesh the burden of proof lies upon the prosecution or victim in a criminal proceeding. There is hence no comprehensive law securing rights and participation of victims in criminal justice system though few supports exist for them. In accessing the justice system, victims face numerous challenges and the plight of crime victims continues to go from bad to worse. In this background, the research relies on qualitative methods to explore their status, participation and challenges in the justice system and lastly recommends how to make the justice system victim oriented.